Multi-point path planning based on the algorithm of colony-particle swarm optimization - Lijue LIU; Shuning LUO; Yan GAO; Meifei CHEN (Tongxin xuebao, 2019)
The problem of multi-point path planning is a NP-hard problem,which is equivalent to finding the shortest path of a starting point and some specific node.Aiming at the problem of multi-point path planning,a retrospective ant colony-particle swarm optimization algorithm was proposed.This algorithm used Floyd-Warshall to transform the graph and combined ant colony algorithm and particle swarm algorithm to find the shortest path.The experimental results show that this algorithm can find the precise solution under small data,at the same time,under a large amount of data,can be better than the maximum minimum ant colony algorithm and genetic algorithm.